Learning Scenarios for the Subject Methodology of Programming From Evaluating the Computational Thinking of New Students - Rojas-López, Arturo; García-Peñalvo, Francisco José (IEEE-RITA, 2018)
Computational thinking is a cognitive process that allows generating solutions to problems through the use of skills, such as abstraction, decomposition, and algorithmic design. This paper presents the proposal to evaluate computational thinking of new students to relate knowledge indicated in the subject methodology of programming and to offer an initial environment of learning. This paper describes the exercises selected to evaluate the previously mentioned skills, and correspondence between the different contents of the course; using a qualitative methodology, the experiences of 65 students were evaluated. The results obtained favored activity carried out, and they also indicated improvements for future generations.